Imaging and Clinical Outcomes Six Months After Middle Meningeal Artery Embolization with Squid for Chronic Subdural Hematoma: A Prospective Study - Ángela H. Schmolling; Carlos Pérez-García; Isabel Bérmudez; Alfonso López-Frías; Eduardo Fandiño; Carmen Trejo; Santiago Rosati; Daniel Padrón; Lara Guardado; José Carlos Méndez; Juan Arrazola; Manuel Moreu (Diagnostics)
Background: Chronic subdural hematoma (CSDH) is a common condition in older adults with rising rates of incidence. While burr hole drainage remains the standard treatment, it is associated with significant recurrence and complications. This study assesses MMA embolization with Squid, both as a standalone procedure and as an adjunct to surgery. Methods: Our prospective registry included 101 patients with 134 CSDH cases treated at two tertiary care centers from December 2020 to January 2024. Patients were divided into two groups: embolization alone and embolization combined with surgery. Demographic, clinical, radiological, and procedural data were collected. Follow-up imaging was conducted at 1, 3, and 6 months. Treatment failure was defined as rescue surgery, hematoma thickness ≥ 10 mm, midline shift > 3 mm at 6 months, or procedure-related death. Results: Fifty-two patients (51.5%) underwent combined treatment, and forty-nine (48.5%) received embolization alone. Most were men (68.3%) and the median age was 82 years. Combined-treatment patients had larger hematomas and more symptoms. Procedures were performed under general anesthesia in 72.3% of patients, with radial and femoral access used equally frequently, and 32.7% underwent bilateral embolization. Patients’ hematoma thickness in follow-up imaging showed a significant decrease (p = 0.000), reaching a median of 0 mm at six months, with no significant difference between groups. Complications occurred in 5.9%, and treatment failure in 4%. Mortality was higher in the embolization-only group, likely reflecting greater rates of comorbidities. Conclusions: This study supports the use of MMA embolization with Squid as a safe and effective treatment for CSDH. Comparable procedural and radiological outcomes in both groups suggest embolization alone may suffice in select patients, offering a less invasive alternative.